A new design of friction test rig and determination of friction coefficient when warm forming an aluminium alloy. (2017) - Shi, Z.; Wang, L.; Mohamed, M.; Balint, D.S.; Lin, J.; Stanton, M.; Watson, D.; Dean, T.A.
Abstract: To facilitate reduced fuel consumption and increase environmental friendliness, in recent years, demands for lightweight vehicles have been increasing, and interest in hot or warm forming of sheet aluminium alloys for use in vehicle body structures, has grown. For better understanding and optimisation of the forming processes, knowledge of friction coefficient between tooling and work-piece, at elevated temperature, is critical. However, because of difficulties with measurement at elevated temperature, most studies on friction are limited to room temperature. In this study, a friction rig was designed for isothermal tests at elevated temperature. The test rig enables pure sliding between pins (made of a tool steel) and a metal sheet. The friction behaviour of Forge Ease 278, a water based solid lubricant pre-applied to aluminium alloy AA5754, was investigated, under isothermal warm forming conditions, using the test rig. The effects of testing temperature, sliding speed and applied pressure on the friction coefficient were studied. It was found that Forge Ease produced a low friction coefficient of around 0.05, above room temperature and below 250 °C. The lubricant performance degrades at 350 °C and the friction coefficient increases markedly. Both sliding speed (up to 150 mm s -1 ) and applied pressure (up to 12.8 MPa) had no significant effect on friction coefficient of Forge Ease.